Experts` successful psychomotor performance was characterized by effective switch of motor and attentional control - Wang, K.-P.; Cheng, M.-Y.; Chen, T.-T.; Chang, Y.-K.; Hung, T.-M.; Ren, J. (Psychology of Sport and Exercise, 2019)
Objectives: This study proposed that Mu (8-13 Hz) and SMR (12-15 Hz) readings in the sensorimotor cortical area can be used to investigate the cognitive mechanisms underlying optimal motor performance. Design: This study used a within-subject design. Method Forty expert golfers were recruited to perform 60 putts while their EEGs were recorded. The putting distance was chosen to ensure that approximately 50% of all putts would be missed so that there was a need for constant adjustments to be made during performance. Successful performance was defined as the ball going in the hole. Results: (a) Lower Mu power in Cz, and alpha power in Pz and Oz were observed for successful performances compared with unsuccessful performances at T1 (-2000 ~ -1000 ms); (b) Higher SMR power in Cz was observed for successful performances relative to unsuccessful performances at T2 (-1000 ~ 0 ms). Conclusions: These findings not only support the multi-action plan model (MAP) and the psychomotor efficiency hypothesis, but also reveal the temporal dynamics of the cognitive mechanisms in an optimal-controlled state.